Partial LVAD Restores Ventricular Outputs and Normalizes LV but not RV Stress Distributions in the Acutely Failing Heart in Silico. Issue 8 (August 2016) - Sack, Kevin L.; Baillargeon, Brian; Acevedo-Bolton, Gabriel; Genet, Martin; Rebelo, Nuno; Kuhl, Ellen; Klein, Liviu; Weiselthaler, Georg M.; Burkhoff, Daniel; Franz, Thomas; Guccione, Julius M.
Purpose: Heart failure is a worldwide epidemic that is unlikely to change as the population ages and life expectancy increases. We sought to detail significant recent improvements to the Dassault Systèmes Living Heart Model (LHM) and use the LHM to compute left ventricular (LV) and right ventricular (RV) myofiber stress distributions under the following 4 conditions: (1 ) normal cardiac function; (2 ) acute left heart failure (ALHF); (3 ) ALHF treated using an LV assist device (LVAD) flow rate of 2 L/min; and (4 ) ALHF treated using an LVAD flow rate of 4.5 L/min. Methods and Results: Incorporating improved systolic myocardial material properties in the LHM resulted in its ability to simulate the Frank-Starling law of the heart. We decreased myocardial contractility in the LV myocardium so that LV ejection fraction decreased from 56% to 28%. This caused mean LV end diastolic (ED) stress to increase to 508% of normal, mean LV end systolic (ES) stress to increase to 113% of normal, mean RV ED stress to decrease to 94% of normal and RV ES to increase to 570% of normal. When ALHF in the model was treated with an LVAD flow rate of 4.5 L/min, most stress results normalized. Mean LV ED stress became 85% of normal, mean LV ES stress became 109% of normal and mean RV ED stress became 95% of normal. However, mean RV ES stress improved less dramatically (to 342% of normal values). Conclusions: These simulations strongly suggest that an LVAD is effective in normalizing LV stresses but not RV stresses that become elevated as a result of ALHF.